Actual Studies Expansion of Improving Services: Access And Equity in Early Childhood Education (Ecd) - *, Suharno (Proceeding of International Conference on Teacher Training and Education, 2016)
This study is to analyze and formulate policies and realistic conditional optimization in order to improve equity of access and equity expansion of early childhood education services. The purpose of this study is to describe: (1) the condition of expansion of access services Childhood Education in Pacitan, (2) equity services Childhood Education in Pacitan, (3) the drivers and inhibitors that influence the expansion of access and equity of service Education Childhood in Pacitan, and (4) to recommend strategies (policies) that could be considered in the context of expanding access and equity in Early Childhood Education services in Pacitan, East Java. Methods of collecting and processing / analysis of the data used is descriptive triangulation- method. The analysis of the assessment of actual on increasing the expansion of access and equity of education services a child early (ECD) mentioned above, it can be concluded that: (1) Judging from a study of actual on increasing the expansion of access rules / regulations and linkages with other institutions / departments / agencies Another quite satisfactory (98%), meaning that there has been a tangle of functional coordination among agencies involved in supporting of existent kindergarten / early childhood. But in terms of availability / supportingÂ  facilities and infrastructure that already over half (67%) driven by the school committee, the hamlets and villages, and related agencies. The support is in the form of building aid, APE (97%), and furniture (67%). About the initiation society is quite high (98%), but in terms of a sense of ownership and take responsibility is still very poor, 90% of citizens still find it hard to pay tuition fees, and (2) From the equalization of educational services children early (ECD) that most of the organizers kindergarten / early childhood has bagged operating licenses (98%). It is also seen a lot of ease in handling licensing for prospective organizers. While the equalization mechanism of early childhood services is through the empowerment of community leaders and village cadres and related agencies (68%). Service forms of early childhood education is to coordinate the various parties, including by head hamlet (42%), village heads (97%), UPT TK-SD ((88%), and the Department of State as many (97%). The criteria of service of public initiatives is still low (54%), but the government instructions may be quite good (67%). While the form of community participation is still low (41%). Award (reward) is still low, at around 41%. However, the contribution of the school committee high enough in the form of aid that are instantaneous (91%). The problem of rights, there are still many children who have not been fortunate to get the rights of educational services kindergarten / early childhood education (58%), the obligation was as big enough (75%), while the responsibility responsibilities of the parties involved is quite high (95%), and the conformity between the access and equity of services is still at the top enough (65%).